Gender Diversity Index - preliminary considerations and results - Laure Humbert, Anne; Gunther, Elisabeth (Cranfield University, 2017)
In this report we outline the preliminary concept for the Gender Diversity Index.
Keywords: 'Composite Indicators'; 'gender composition'; 'Gender Studies'; 'Team Effectiveness'; 'Performance assessment'; 'Composite Measures'; 'Higher Education'; 'Industry Economics and Industrial Organisation'; 'Business and Management not elsewhere classified'; 'Human Resources Management'; 'Statistics'; 'Statistics not elsewhere classified'; 'Gender studies'